Pengaruh Brand Image, Expertiential Marketing, Dan Product Quality Terhadap Customer Loyalty Merek Tropicana Slim Pada Premium Community - Megaria Damanik; Beby Karina Fawzeea Sembiring; Rini, Endang Sulistya; Arif Qaedi Hutagalung (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
One of the strategies used by Tropicana Slim to win the Top Brand Award for 4 (four) consecutive years is to enter the premium community through brand activation. This research aims to determine and analyze the influence of brand image, experiential marketing, and product quality on customer loyalty of the Tropicana Slim brand in the premium community. This research is associative research and the type of data used is quantitative. The population in this study are members of the premium community. The number of samples in the research was 95 people using a purposive sampling technique with the following criteria: they are premium community members who have experienced brand activation by Tropicana Slim Medan City and have purchased Tropicana Slim products at least 1 (one) time. The data analysis used is multiple linear regression analysis. The results of this research show that simultaneously brand image, experiential marketing and product quality have a positive and significant effect on customer loyalty of the Tropicana Slim brand in the premium community. Partially, brand image, experiential marketing and product quality have a positive and significant effect on customer loyalty of the Tropicana Slim brand in the premium community.